2020
DOI: 10.1111/cen.14143
|View full text |Cite
|
Sign up to set email alerts
|

Australian endocrinologists need more training in transgender health: A national survey

Abstract: Objective An increasing number of trans and gender diverse (TGD) individuals are seeking gender‐affirming hormone therapy for gender transition. Little is known about the levels of training, experience and confidence of endocrinologists in providing care and lack of training and experience is a potential barrier to individuals seeking appropriate and timely health care. We aimed to assess the level of training and confidence of Australian endocrinologists and trainees in the endocrine management of trans and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…similarly high rate of exclusion is seen in existing scoping reviews, 1,44 and although we could not locate any international scoping reviews on the topic, a similar paucity of transgender health training is reflected in the primary literature worldwide. 1,[13][14][15][16] Future studies utilising a modified-Delphi method 50 This…”
Section: It Is Critical That Any Educational Interventions Delivered ...mentioning
confidence: 99%
See 1 more Smart Citation
“…similarly high rate of exclusion is seen in existing scoping reviews, 1,44 and although we could not locate any international scoping reviews on the topic, a similar paucity of transgender health training is reflected in the primary literature worldwide. 1,[13][14][15][16] Future studies utilising a modified-Delphi method 50 This…”
Section: It Is Critical That Any Educational Interventions Delivered ...mentioning
confidence: 99%
“…1,[13][14][15][16] This paucity of transgenderspecific curricula in undergraduate and postgraduate training programmes has perpetuated physician inexperience and discomfort with the provision of care to transgender populations, leading to transgender patients being denied care, avoiding health care environments when they need care, and experiencing the added burden of needing to advocate for themselves to receive equitable care. [13][14][15]17 In a recently published Trans PULSE Canada survey of transgender Canadians, over 45% had one or more unmet health needs in the past year. 7 Transgender health gaps are perpetuated and even widened by the health care system.…”
Section: Introductionmentioning
confidence: 99%
“…Respondents also reported that only 4% received training on TGD care in medical school. However, 91% indicated a desire for additional training [20].…”
Section: Training and Medical Educationmentioning
confidence: 99%
“…At the same time, implementing TGD-related training curricula, supervision, and consultations for HCPs online could advance professionalization in trans health care and further reduce barriers resulting from stigma [14][15][16]. The need to train HCPs extends to all health care disciplines, from primary care to nursing, whose practice-based training curricula should enable them to work from a TGD-informed standpoint [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%